Determining the Critical Particle Size to Induce Enhanced Emission in Aggregates of a Highly Twisted Triarylamine. Issue 16 (2nd October 2013) - Kokil, Akshay; Chudomel, J. Matthew; Yang, Boqian; Barnes, Michael D.; Lahti, Paul M.; Kumar, Jayant
<x xml:space="preserve">Abstract</x> Towards highly luminescent aggregates: A highly twisted triphenylamine displays aggregation‐induced enhanced emission. A solvent‐specific critical molecular aggregate size, once reached, gives rapid onset of enhanced emission in polar solvent mixtures that favor quenching of solvated individual molecule excited states.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>